1982
DOI: 10.1002/path.1711380207
|View full text |Cite
|
Sign up to set email alerts
|

Towards economy of effort in quantitative ultrastructural pathology: Efficient sampling schemes for studying experimental carcinogenesis

Abstract: Hamster cheek pouch mucosa was painted with DMBA in order to compare samples of epithelium at different pathological stages of carcinogenesis. Stereological methods were applied to ultrathin sections of tissue to estimate one ultrastructural index of change, the surface ratio of lamina densa compared with the overlying plasma membrane of cells in stratum basale. Analysis of variance techniques were then employed to isolate and quantify the contributions which different levels of sampling (animals, tissue block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1983
1983
1995
1995

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…With these techniques, it is possible to quantify the importance of biological variation as a contributor to total observed variance. In those systems for which information is currently available, biological variation has proved to be either of no consequence (Gundersen & Plsterby, 1980) or a major determinant of overall variance (Shay, 1975;Gundersen & Plsterby, 1980, 1981Mayhew et al, 1982). In this report, we adduce further evidence to support the contention that biological variation can be the decisive factor influencing the overall precision of morphometric estimates obtained from nested sampling designs.…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations
“…With these techniques, it is possible to quantify the importance of biological variation as a contributor to total observed variance. In those systems for which information is currently available, biological variation has proved to be either of no consequence (Gundersen & Plsterby, 1980) or a major determinant of overall variance (Shay, 1975;Gundersen & Plsterby, 1980, 1981Mayhew et al, 1982). In this report, we adduce further evidence to support the contention that biological variation can be the decisive factor influencing the overall precision of morphometric estimates obtained from nested sampling designs.…”
Section: Introductionsupporting
confidence: 68%
“…For instance, in the hamster cheek pouch model we have found that biological variation accounts for only about 30? (, of overall variance when the nested design described in this study (example D) is applied to hyperplasia and dysplasia groups (Mayhew et al, 1982). In part this dilution of the influence of biological variation reflects an appreciable intermicrograph variation which may be partially attributable to too high a final print magnification.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…For the purpose of our investigation, blood vessels were defined as those structures lined by endothelial cells which might contain erythrocytes. A stratified systematic random sampling procedure was adopted [19,26]. Table 1 summarises the sampling strategy adopted in this study.…”
Section: Morphometric Proceduresmentioning
confidence: 99%